2014
DOI: 10.3748/wjg.v20.i46.17618
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofHelicobacter pyloriinfection among the healthy population in Iran and countries of the Eastern Mediterranean Region: A systematic review of prevalence and risk factors

Abstract: The prevalence of H. pylori in EMRO countries is still high in the healthy asymptomatic population. Strategies to improve sanitary facilities, educational status, and socioeconomic status should be implemented to minimize H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 45 publications
4
89
2
1
Order By: Relevance
“…Zelenkova had reported a prevalence of H. pylori to be lower in diabetics compared to non-diabetic controls (27% vs. 51%) [27,28]. In other studies, the prevalence of H. pylori infection was comparable between diabetic and control [10][11][12][13][14][15][16][17]. In our study we found no significant association between H. pylori and diabetes (p=0.979).…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…Zelenkova had reported a prevalence of H. pylori to be lower in diabetics compared to non-diabetic controls (27% vs. 51%) [27,28]. In other studies, the prevalence of H. pylori infection was comparable between diabetic and control [10][11][12][13][14][15][16][17]. In our study we found no significant association between H. pylori and diabetes (p=0.979).…”
Section: Resultscontrasting
confidence: 52%
“…The prevalence of H. pylori colonization is about 30% in the United States and other developed countries as opposed to >80% in many developing countries [16]. In general, the overall prevalence of H. pylori infection in the Middle East, irrespective of time and age groups, ranged from 22% to 87.6% [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin is the major storage protein in the body for iron and the most powerful marker for diagnosis of iron deficiency anemia [62]. Ferritin is affected by iron deficiency as it reaches to 12-15 ng/ml without concomitant inflammation and to move than 50 ng/ ml with concomitant inflammation [63].…”
Section: Kotob Et Almentioning
confidence: 99%
“…Helicobacter pylori is an important gastroduodenal pathogen of humans (Larsen et al, 2013) and its infection is a growing public health problem with a prevalence rate of approximately 50%, especially in the developing countries (Eshraghian, 2014;Nagy et al, 2016;Roberts, 2016). The infection by H. pylori when acquired in childhood and it will persist through life if a successful antimicrobial regimen is not performed (Mcnulty et al, 2012;Arslan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%